(3TQM QSGdI GdhdOjIs - (3GdBeOj, YHO GdhgGH Hf MSjf Hf hdi GdOjf, cGf MjG (B1190(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj COHfG HBOGH GdefGXQjf (B...(3deG cGfJ GdQSGdI GdhdOjI aj GdBOGH eJOGhdI Hjf Chdj GdCdHGH LGeYI dbhGYO GdefGXQjf aj gPG GdHGH hcGfJ SgdI GdeCNP ddeHJOFjf hbO JUOi dTQMgG eYGTQG ef GdCMHGH (B...s
(3BNQgG (B:s
... (3EP dG jLH Ydi GdeYdd EdG GdGKHGJ hYfO GdGKHGJ jXgQ GdUhGH HNdGa SGFQ GdhXGFa hef CQGO GdGSJbUGA hGdHdhZ Edi GdZGjI aj eYQaI af GdefGXQI aYdjg Cj ajdRe HQSGdJfG GdeYehdI GdeDdaI dJbQjQ bhGfjf GdefGXQI (B... (3JeJs
(3JHUQI GdYfhGf (B:s
(3GdhdOjI dSGLbdj RGOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf (B1\643s
(3gOjI GdYGQajf (B1\643s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs